FORMS, MODELS AND MECHANISMS OF PUBLIC-PRIVATE PARTNERSHIPS IN THE SERVICE SECTOR - Utemuratova Gulnarakhan Khojaniyazovna (American Journals, 2024)
In this article, the forms of public-private partnership, the main directions of economic activity between state and private business entities, the main forms of public-private partnership in the service sector, the main features specific to this system, the role of public-private partnership in the system of interaction between the public and private sectors and its outsourcing of public services and its differences from the state franchise are explored.
Keywords: Service sector, public-private partnership, project, public services, outsourcing, franchising.